Abnormal expression of ephrin-A5 affects brain development of congenital hypothyroidism rats. Issue 11 (1st August 2018) - Suo, Guihai; Shen, Feifei; Sun, Baolan; Song, Honghua; Xu, Meiyu; Wu, Youjia
Abstract : EphA5 and its ligand ephrin-A5 interaction can trigger synaptogenesis during early hippocampus development. We have previously reported that abnormal EphA5 expression can result in synaptogenesis disorder in congenital hypothyroidism (CH) rats. To better understand its precise molecular mechanism, we further analyzed the characteristics of ephrin-A5 expression in the hippocampus of CH rats. Our study revealed that ephrin-A5 expression was downregulated by thyroid hormone deficiency in the developing hippocampus and hippocampal neurons in rats. Thyroxine treatment for hypothyroid hippocampus and triiodothyronine treatment for hypothyroid hippocampal neurons significantly improved ephrin-A5 expression but could not restore its expression to control levels. Hypothyroid hippocampal neurons in-vitro showed synaptogenesis disorder characterized by a reduction in the number and length of neurites. Furthermore, the synaptogenesis-associated molecular expressions of NMDAR-1 (NR1), PSD95 and CaMKII were all downregulated correspondingly. These results suggest that ephrin-A5 expression may be decreased in CH, and abnormal activation of ephrin-A5/EphA5 signaling affects synaptogenesis during brain development. Such findings provide an important basis for exploring the pathogenesis of CH genetically.